Resource public key infrastructure RPKI: status and problems - Yingying SU; Dan LI; Honglin YE (Dianxin kexue)
The BGP (border gateway protocol) did not fully consider security issues at the beginning of its design.With the rapid growth of the Internet, its security risks have become incrementally obvious.Academia and industry have proposed many solutions to the security issues faced by inter-domain routing, and what is really deployed is the RPKI (resource public key infrastructure) promoted by the IETF (the Internet Engineering Task Force).The development status and research advances of RPKI were surveyed, with emphasis on problems of RPKI, existing solutions, and related limitations.Moreover, latest achievements on RPKI function extension were introduced.Finally, future research directions were concluded.